Library Services for Adults in the 21st Century - Okobi, Elsie A. Rogers Halliday (Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2014)
"Develop the competencies needed to provide effective adult services in modern public libraries with this comprehensive guidebook"--
Keywords: Adult services in public libraries; United States; United States; Libraries and adult education; United States; Libraries and community; United States; Public services (Libraries); dept.ils; faculty_collection

Social indexing: A solution to the challenges of current information organization - Choi, Y. (Libr. Inf. Sci., 2014)
Purpose - This chapter aims to discuss the issues associated with social indexing as a solution to the challenges of current information organization systems by investigating the quality and efficacy of social indexing. Design/methodology/approach - The chapter focuses on the study which compared indexing similarity between two professional groups and also compared social tagging and professional indexing. The study employed the method of the modified vector-based Indexing Consistency Density (ICD) with three different similarity measures: cosine similarity, dot product similarity, and Euclidean distance metric. Findings - The investigation of social indexing in comparison of professional indexing demonstrates that social tags are more accurate descriptions of resources and reflection of more current terminology than controlled vocabulary. Through the characteristics of social tagging discussed in this chapter, we have a clearer understanding of the extent to which social indexing can be used to replace and improve upon professional indexing. Research limitations/implications - As investment in professionally developed web directories diminishes, it becomes even more critical to understand the characteristics of social tagging and to obtain benefit from it. In future research, the examination of subjective tags needs to be conducted. A survey or user study on tagging behavior also would help to extend understanding of social indexing practices. © 2013 by Emerald Group Publishing Limited.
Keywords: dept.ils

Web 2.0 applications' usage and trends in top US academic libraries - Boateng, Frank; Liu, Yan Quan (Library Hi Tech, 2014)
Purpose - This paper aims to explore Web 2.0 technologies usage and trends in the top 100 US academic libraries as exemplified through the academic library websites. Design/methodology/approach - The top 100 universities were selected from the US News & World Report's (USNWR) 2013 ranked list's top 100 of the best colleges in the USA. Content analysis was used in terms of quantitative approach. A checklist was developed as the main research instrument based on other checklists and questionnaires. Each of the selected university library websites was visited within a period of two weeks to explore implementation and usage of web tools, including SNS, blog, RSS, wikis, podcast/vodcast, and social bookmarking/tagging. Findings - All 100 academic libraries had a social media presence on Facebook and Twitter, making SNS the most widely applied Web 2.0 tool. The wild was the least applied Web 2.0 technology, with a 34 percent participation rate. Blog was the second most popular tool with a 99 percent participation rate, followed by RSS and IM/Chat with 97 percent and 91 percent respectively. The vodcast and podcast had 47 percent and 46 percent participation rates respectively, while social bookmarking/tagging were also used by 39 percent of the academic libraries. Research limitations/implications - This study is completely based on publicly available data regarding usage of Web 2.0 applications. Web 2.0 tools used on library intranets were not analyzed for this study. Outcomes suggest that academic libraries are increasingly using Web 2.0 applications to promote themselves, enhance library services, and highlight resources to patrons. Originality/value - This is the first research that draws an overall picture of the usage and trends of Web 2.0 applications in the top 100 US academic libraries. This study demonstrates some noticeable patterns regarding usage, trends, and adoption which are relevant to how Web 2.0 applications are perceived and used within academic libraries. The study provides academic libraries with helpful information to better meet their user needs by effectively applying Web 2.0. Additionally, library managers, librarians and other libraries may also find this research beneficial as they plan to deploy Web 2.0.
Keywords: Academic libraries; Library services; Technology usage; Web 2.0; dept.ils; peer-reviewed

From siloed data to linked data: Developing a social metadata repository - Choi, Yunseon (Wiley, 2014)
Although social data has been investigated and discussed regarding its impact on indexing and retrieval performance on the web, there has been little research conducted on storing or linking social data and identifying bibliographic relationships among social data for further use of social data. In this paper, we discuss our work in progress that aims to develop a social metadata repository which would be an important implication for making social data more valuable and reusable for searching and retrieval. We describe FRBR (Functional Requirements of Bibliographic Records) conceptual model's Entity-Relationship (ER) view on bibliographic relationships and demonstrate how social metadata are encoded in RDA (Resource Description and Access) and how the implicit bibliographic relationships of social data are explicitly represented as RDF (Resource Description Framework) triples (Subject - Predicates - Objects) with links to external sources. We believe that the shareable and linked metadata repository of social data is remarkably significant, not only because it supports the accessibility to related documents, but also because it is clarifying the implicit semantic relationships among social data.
Keywords: FRBR; Linked Data; Metadata; RDA; RDF; Social data; Social tags; dept.ils